تسجيل بعض الإصابات الفطرية عند الصيصان في فترة الحضانة بسبب التلوث الفطري للفرشة - نيصافي, علي (Latakia University Journal -Biological Sciences Series, 2019)
تعد الإصابات الفطرية من المشكلات الصحية الهامة التي تعترض قطاع إنتاج الدواجن في سورية ولا توجد أية دراسة محلية تثبت وجود مثل هذه الإصابات أو التسممات الفطرية عند الطيور ، رغم الاشتباه بوجود حالات مختلفة من التسممات الفطرية الحادة أو المزمنة في مزارع الدواجن. سجلت في هذا البحث خمس حالات ، أربعة منها في محافظة اللاذقية وواحدة في محافظة ادلب منطقة جسر الشغور, لوحظت في ثلاث حالات أعراض سريرية حادة ومبكرة بدءا من اليوم الثاني والثالث من عمر الصيصان ترافقت بنسبة نفوق مرتفعة جدا في المزرعة الأولى ( الدروقيات ) والمزرعتين الثانية والثالثة في (الرويمية) ونسبة نفوق أقل حدة وارتفاعا في كل من مزرعتي جبلة وجسر الشغور ومن خلال الفحوص السريرية والتشريحية والمخبرية للصيصان المصابة وللفرشة تبين إصابة الفرشة بثلاثة أجناس من الفطور. Fungal infections are considered among the important health problems confronting poultry production sector in Syria. There isn’t any local study that confirms the presence of such infections or Mycotoxicosis in birds, despite doubting the presence of different acute and chronic intoxication cases in poultry farms. In this research, five cases have been recorded, four of which are in the Lattakia Governorate and one case in the Idleb Governorate. Acute and early clinical symptoms were observed in three cases, starting from the second and third day of the chickens’ life, which had been accompanied with very high perishing rate in the first farm (Al-Drouqiyyat) and the second and third farms in (Al-Rwaymiyyeh), with a less acute and lower perishing rate in both Jableh and Idleb farms. It was observed through the clinical, anatomic, and laboratory tests of the affected chickens and litter that the litter is infected with three genera of fungi.